2020
DOI: 10.22226/2410-3535-2020-2-200-205
|View full text |Cite
|
Sign up to set email alerts
|

Preparation of CdSe / RGO-GO composites with the high performance of adsorption and degradation

Abstract: Nowadays, dyes are usually chemically stable, can not be degraded naturally within a short time, and easy to migrate along with water, which is the main source to influence the health of human beings and to destroy the ecosystem. Based on that, in this work a high-performance photocatalyst was prepared successfully by an organic synthesis method. The obtained photocatalyst contained numerous nanoscale heterojunctions, which consisted of CdSe nanoparticles scattered on the partially reduced graphene oxide (name… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 20 publications
0
2
0
Order By: Relevance
“…The search for graphene/metal composites is a new and actively developing branch of composite technologies [ 1 , 2 , 3 , 4 ]. The main component of these composites is graphene, which has low weight, high strength, and flexibility, as well as high electrical and thermal conductivity [ 5 , 6 , 7 , 8 , 9 ]. Such unique properties of graphene, added to the metal matrix, lead to the formation of composites with special properties that have use for future applications.…”
Section: Introductionmentioning
confidence: 99%
“…The search for graphene/metal composites is a new and actively developing branch of composite technologies [ 1 , 2 , 3 , 4 ]. The main component of these composites is graphene, which has low weight, high strength, and flexibility, as well as high electrical and thermal conductivity [ 5 , 6 , 7 , 8 , 9 ]. Such unique properties of graphene, added to the metal matrix, lead to the formation of composites with special properties that have use for future applications.…”
Section: Introductionmentioning
confidence: 99%
“…% [10]. Therefore, many theoretical and experimental works have been carried out to find ways to increase the sorption capacity of carbon structures [11][12][13][14][15][16][17][18][19][20]. These works have demonstrated that reduction of the temperature and increasing of pressure have a very positive effect on the hydrogen storage by carbon structures.…”
Section: Introductionmentioning
confidence: 99%